THE IMPACT OF INFORMATION AND COMMUNICATION TECHNOLOGY ON ROAD FREIGHT TRANSPORTATION - Ryuichi YOSHIMOTO (IATSS Research, 2005)
Surveying the recent trend toward e-commerce and computerization in the trucking industry, this paper establishes a framework for analyzing the impact of information and communication technology on road freight transportation in terms of commerce, logistics and fleet management, and proposes hypothetical mechanisms of influence. The authors note that the rapid growth of e-commerce and freight fleet management systems make it difficult to arrive at firm, statistics-based conclusions about their impact on road freight transportation, but suggest that more sophisticated government management of transportation demand as well as freight fleet management systems could cancel out the negative impact of e-commerce on road transportation.